Answer:
28-4x
Step-by-step explanation:
Step 1: Open most inner bracket and simplify
=18-2(x+x-5)
=18-2(2x-5)
Step 2: Expand brackets by multiplying 2 in and simplify
=18-2(2x)-2(-5)
=18-4x+10
=28-4x
Therefore the answer is 28-4x
Answer:
D 0.61
Step-by-step explanation:
0.42
0.69
= 0.6089
(x + y)^2 = (x^2 - 2xy + y^2)
First distribute the ^2 on the left side of the equation to each term inside the parenthesis:
x^2+ 2xy + y^2
Now pick one of the variables to solve for and isolate it:
(solving for x)
x^2 + 2xy + y^2 = x^2 - 2xy + y^2
x^2+ 2xy = x^2 - 2xy
2xy = -2xy
-x = x
x = 0
When you solve for y in the equation it will turn out to be 0 as well
Answer:
1,459
You have to divide
7,295÷5 and u get your answer
Answer:
the second one
Step-by-step explanation: